2015
DOI: 10.5604/20834543.1142351
|View full text |Cite
|
Sign up to set email alerts
|

Mild adverse events after administration of iodinated contrast agent in computed tomography examination

Abstract: Wprowadzenie. Środki kontrastujące (ŚK) w tomografii komputerowej (TK) ułatwiają różnicowanie pomiędzy poszczególnymi tkankami. Jednym z najczęściej stosowanych preparatów jest Ultravist (Iopromid), jodowy monomer rozpuszczalny w wodzie. Specyfiką środków kontrastujących jest możliwość wystąpienia u pacjenta reakcji niepożądanych o różnym charakterze. Reakcje łagodne są bardzo rzadko opisywane w literaturze radiologicznej. Cel pracy. Celem pracy była analiza lekkich powikłań po podaniu jodowego środka kontrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…During intravenous contrast injection, the most common sensation reported by both men and women was a feeling of spreading warmth throughout the body. A study by Wyszomirska E. et al that analyzed mild adverse events after the administration of iodine as a contrast agent confirms the result obtained in our study [4]. Another sensation that occurred in 41.1% of women was a metallic taste in the mouth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…During intravenous contrast injection, the most common sensation reported by both men and women was a feeling of spreading warmth throughout the body. A study by Wyszomirska E. et al that analyzed mild adverse events after the administration of iodine as a contrast agent confirms the result obtained in our study [4]. Another sensation that occurred in 41.1% of women was a metallic taste in the mouth.…”
Section: Discussionsupporting
confidence: 91%
“…The third most frequently indicated symptom was a feeling of pressure on the urinary bladder, which occurred in 64.2% of men and 22.1% of women. In contrast to their own study, in the analysis by Wyszomierska et al women indicated a feeling of urination more often than men did [4].…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations